Motorsports management: opportunities, issues and challenges - Syarizal Abdul Rahim; Norailis Ab. Wahab (2013)
The collaboration between FASTrack Autosports Pte. Ltd. (Singapore) and UEM Land Berhad (Malaysia) to build a RM3.5 billion Motorsports City in Johor’s Iskandar region provides greater prospects for the nation and to motorsports devotees. Hence, this paper aims to focus on certain motorsports issues including its opportunities and challenges. It commences with the development of motorsports in Malaysia. Although, this paper is constrained by the paucity of academic literatures on motorsports from the management perspective however, together with the results of interview from two key people in the motorsports industry and the authors’ experience with practitioners in the respective business, some issues that came to light are pointed out including organizational and human resource. On the basis of the authors’ understanding of the progressively multifaceted activities of this industry, much attention needs to be focused on the opportunities of this sport and some issues are demanding immediate actions. More awareness needs to be given to motorsport events as well as increased research efforts on this industry. Significant findings from the management perspectives perhaps might influence policy making and practice inside the track.